The differences in symptom networks of depression, anxiety, and sleep in college students with different stress levels - Wei Li; Shuhui Huo; Fei Yin; Zhengyu Wu; Xueqi Zhang; Zhengjun Wang; Jianqin Cao (BMC Public Health)
Abstract Background Stress is closely related to depression, anxiety, and sleep problems. However, few studies have explored the complex symptom-level relationships among these variables at different stress levels among college students. Methods From March to April 2024, a survey was conducted using a convenience sampling method in three universities in Daqing City, Heilongjiang Province. A total of 7,845 participants (2,447 males and 5,398 females) were assessed using the Psychological Stress Tolerance Index (PSTR), the General Health Questionnaire-20 (GHQ-20), and the Self-Rating Scale of Sleep (SRSS). Based on the GHQ-20 scores, college students were categorized into low, medium, and high-stress levels. Non-parametric tests and Post-hoc tests were conducted to explore the impact of stress levels on depression, anxiety, and sleep. Network analysis methods were used to reveal the differences in the symptom networks of depression, anxiety, and sleep among college students at different stress levels. Results Non-parametric test results indicate significant differences in depression, anxiety, and sleep scores among high, medium, and low-stress groups. Post-hoc tests reveal that the high-stress group scores significantly higher in depression, anxiety, and sleep than the medium and low-stress groups. The medium-stress group scored significantly higher than the low-stress group. Network analysis shows that the core symptoms in the low-stress group are “Difficulty falling asleep”, “Anxious and restless”, and “Taking sleeping pills”, with bridging symptoms including “Hopeless future”, “Feeling useless”, “Life is a battlefield”, and “Anxious and restless”. For the medium-stress group, the core symptoms are “Difficulty falling asleep”, “Easily awakened after sleeping”, and “Life is hopeless”, with bridging symptoms including “Feeling useless”, “Life is a battlefield”, “Anxious and restless”, and “Taking sleeping pills”. In the high-stress group, the core symptoms are “Difficulty falling asleep”, “Feeling useless”, and “Anxious and resless”, with bridging symptoms including “Feeling useless”, “Life is a battlefield”, “Anxious and restless”, and “Stress hinders tasks”. Conclusion Stress exacerbates depression, anxiety, and sleep problems among college students, with differences in core symptoms and bridging symptoms of depression, anxiety, and sleep disturbances at varying levels of stress. Therefore, precise interventions can be implemented based on the core and bridge symptoms of the three networks, further improving university students’ physical and mental health.